2020
DOI: 10.1007/s42399-020-00597-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Hospital-Wide COVID-19 Outbreak Affecting Patients and Healthcare Workers

Abstract: To the best of our knowledge, here, we describe the first hospital-wide outbreak of SARS-CoV-2 that occurred in Germany in April 2020. We aim to share our experience in order to facilitate the management of nosocomial COVID-19 outbreaks in healthcare facilities. All patients and hospital workers were screened for SARS-CoV-2 repeatedly. An infection control team on the side was installed. Strict spatial separation of patients and intensified hygiene training of healthcare workers (HCW) were initiated. By the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Some recommendations for tailored NPPIs to maximize efforts to prevent HAIs were noted from the reviewed studies and could be adopted across the globe. These include the following: In all healthcare settings, adherence to strict spatial separation of patient beds and frequent intensified training of healthcare workers are recommended alongside the standard recommended prevention procedures [44]. Cleaning of touch surfaces was suggested to be as frequent as every two hours in order to be effective [45].…”
Section: Recommendations For Preventing Super-spreading Covid-19 In H...mentioning
confidence: 99%
“…Some recommendations for tailored NPPIs to maximize efforts to prevent HAIs were noted from the reviewed studies and could be adopted across the globe. These include the following: In all healthcare settings, adherence to strict spatial separation of patient beds and frequent intensified training of healthcare workers are recommended alongside the standard recommended prevention procedures [44]. Cleaning of touch surfaces was suggested to be as frequent as every two hours in order to be effective [45].…”
Section: Recommendations For Preventing Super-spreading Covid-19 In H...mentioning
confidence: 99%
“…In the case of Hospitals A and B, it was noted that increased fatigue from heavy pressure to perform strict IPC allowed the virus to enter the wards. It was also observed that the infection was acquired in nonclinical settings (i.e., by crossing the lines of traffic between staff, and by conversations in changing rooms and cafeterias without wearing masks or not keeping enough distance) [ 2 , 40 , 44 ]. In Hospital C, it was pointed out that staff may have brought the virus in from outside.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the Covid19 pandemic, patient care in hospitals jumped drastically, causing hospitals to be filled with patients infected with Covid19. Since the emergence of the virus, the handling of Covid19 in hospitals has become stricter, as demonstrated in April 2020, where one of the hospitals in Germany screened patients and workers, formed an infection control team, carried out patient separation and conducted hygiene training for health workers (2). The treatment of Covid19 in hospitals, as recommended by the World Health Organization (WHO), is through screening and triage for patients suspected of Covid19, the use of PPE (Personal Protective Equipment) for health workers as well as training, the implementation of disinfection and environmental sanitation in hospitals, waste management and separation of infected and uninfected patients (3).…”
Section: Introductionmentioning
confidence: 99%